Diversity of Local Responses to Integrated Conservation and Development Projects - Ummus, Rafael Eichemberger (Sustainability in Debate, 2015)
Integrated Conservation and Development Projects, a biodiversity conservation strategy, has been widely adopted by NGOs and international cooperation agencies in recent decades. These projects are characterized by conservation objectives associated with the socioeconomic development of local populations living inside protected areas or in their neighborhoods. In this paper, the author analyzes 25 project evaluations in 18 countries, identifying the spectrum of triggered responses. From this base, 34 different responses were identified, which highlights the potential of these projects to produce changes in local systems. However, in half of the cases (14 of 25), the actions developed by the projects produced no identifiable responses, and among the cases in which responses were effectively observed, many of them appeared to have the potential for counter-productive effects. Results point to the risks associated with these biodiversity conservation interventions, and show the need to approach their design, evaluation and scientific research from a systemic point of view.